Evaluation of optimal medical therapy in acute myocardial infarction patients with prior stroke - Zhang, Dongfeng; Song, Xiantao; Raposeiras-Roubín, Sergio; Abu-Assi, Emad; Simao Henriques, Jose Paulo; D'Ascenzo, Fabrizio; Saucedo, Jorge; González-Juanatey, José Ramón; Wilton, Stephen B; Kikkert, Wouter J; Nuñez-Gil, Iván; Ariza-Sole, Albert; et al. (SAGE Publications, 2021)
Treatment of acute myocardial infarction (AMI) patients with prior stroke is a common clinical dilemma. Currently, the application of optimal medical therapy (OMT) and its impact on clinical outcomes are not clear in this patient population.
Keywords: STEMI; OMT; clinical outcomes